Lengua portuguesa, alma africana: el caso de Mia Couto - Barbara, FRATICELLI (Revista de Filología Románica, 2002)
This article shows one of the most important aspects of the mozambicam writer Mia Couto: the fusion of the cultural and linguistic portuguese element with the african one. His literature is a mix between portuguese language and specific terms used by different mozambican people around the country; Mia Couto knows, in his novels, how to achieve a wise mix between african essence and his Portuguese roots.